CHALLENGES IN SETTING UP A DIGITAL HUMANITIES CENTRE IN ROMANIA - Corina MOLDOVAN (Studia Universitatis Babeş-Bolyai. Philologia, 2017)
Challenges in Setting up a Digital Humanities Centre in Romania. Other than the obvious and well-documented benefits of the Digital Humanities centre, now a common occurrence in western universities, this paper wishes to focus on the very specific challenges encountered by the DigiHUBB team in creating one in Romania. The very first of its kind in this country, the centre was eventually credited by the Babeş-Bolyai University, but yet still struggles due to the fact the domain itself is still no fully recognized on a national scale. Both the issues and the positive aspects, which are indeed many, will be taken into account in showing how a promising this field of research is just as long as scholars and policy-makers keep an open mind.